Human existence is a caring existence - Pegoraro, Olinto (O Mundo da Saúde, 2009)
This paper deals with three ethical conceptions of human beings, namely, the Greek, the Jew-Christian and the Contemporary. In the first one, human dignity resides in the capacity to think: intelligence seemed a divine flash in the matter. The second extends this understanding adding the dimension of faith: reason accepts realities that go beyond it but do not contradict it, for reason could not accept contradiction. The third ethical conception of human beings is based on human existence’s temporality: human beings, as the only known intelligent reality, are understood as carers of themselves (ethics-politics), nature (through science) and history that they lead (through wisdom).